Application of Progressive Law to Marriage Annulment Cases: Prospects and Development in Indonesia's Religious Court - Azmi, Nofan Nurkhafid; Bisri, Hasan; Solehudin, Ending; Saepullah, Usep; Ridwan, Ahmad Hasan (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2024)
Progressive law is based on the emergence of a sense of dissatisfaction with the theory that has been developed and used as a guide in legal practice in Indonesia, legal theories that have been developed so far, are unable to respond to problems that occur in the reality of society. This has resulted in a sense of public dissatisfaction with the performance of the law and the courts. The value of justice is the main goal to be achieved in law enforcement efforts. Meanwhile, in the case of marriage annulment, there are parties who are dissatisfied with the decision of the first level judge, so they take legal action to a higher level court to answer their dissatisfaction. This research uses a qualitative method with an empirical juridical approach. Primary data obtained from marriage annulment decisions Number 185/Pdt.G/2023/PTA.Bdg, 84/Pdt.G/2023/PTA.Bdg and 106/Pdt.G/2023/PTA.bdg, secondary data obtained from laws, journals and other legal books that have the same relevance as this research. After the data is collected, data analysis is carried out to get answers to the problems raised. This research resulted in several findings. First, the application of progressive law in polygamy licensing cases uses the hermeneutic method, namely the school of philosophy that studies the nature of something to understand something into a clearer object of interpretation, in the case of forced marriage using the legal interpretation method, namely a conclusion in providing an explanation or understanding of a term that is unclear in meaning. Second, the door for judges to apply progressive law will never be closed, in fact it is a necessity by judges, legal problems will continue to exist and continue to develop.